Sleep and asthma management in youth with poorly-controlled asthma and their caregivers: a qualitative approach. (3rd June 2022) - Evans, Corinne; Fidler, Andrea; Baker, Dawn; Wagner, Mary; Fedele, David
Abstract: Objective: Youth with poorly-controlled asthma are at increased risk for sleep disturbances caused by nocturnal symptoms like coughing. Asthma-related sleep disturbances can have downstream consequences for youth with asthma and their families. This study aims to describe (1) sleep disturbances in adolescents with poorly-controlled asthma and their caregivers and (2) the relationship between sleep and asthma management. Methods: Adolescents with poorly-controlled asthma and their caregivers completed the Family Asthma Management System Scale (FAMSS), a semi-structured interview that assesses youth asthma management within the family context. Interviews were audio-recorded and transcribed. Two authors coded each transcript for sleep-related data in NVivo using descriptive content analysis. Results: Thirty-three adolescents ages 12–15 years old ( M = 13.2, SD = 1.2) with poorly-controlled asthma and their caregivers participated in this study. Four main themes emerged: sleep difficulties, sleep environment, sleep and self-management, and fatigue and self-management. 42% of youth and caregivers reported worse nocturnal asthma symptoms (e.g. coughing) that caused frequent nighttime awakening. Approximately 27% of caregivers expressed distress over their child's nocturnal asthma and described their management strategies (e.g. co-sleeping, nighttime symptom monitoring). Adolescents described sleepiness as a barrier to asthma self-management tasks (e.g. medication adherence, response to exacerbation). Conclusion: Interview responses demonstrated the considerable interrelationship of sleep and asthma management in adolescents with poorly-controlled asthma. Asthma providers should consider discussing sleep difficulties with their adolescent patients and their families. Addressing these difficulties may help adolescents improve their asthma self-management and help caregivers better cope with their child's disease.